Part-Load Simulation of Combined Cycle and Gas Turbine Power Plants Using DWSIM - Hassan, Twana N.; Manji, Saif T.; Maaroof, Ahmed A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
In Iraq, combined cycle gas turbine (CCGT) systems are the only and main process for power generation (electricity). Due to its importance and significance, accurate simulation is crucial for evaluating the process performance under different operation conditions. In this study, DWSIM software, open-source simulation tool, was used for modeling and assessing CCGT performance during part-load circumstances. This software used for its reliability in capturing operational behavior. The methodology consists of simulating CCGT response under the variation of the power by integrating part-load performance equations into DWSIM software. Generally, two cases included in this work; the first case covered a DWSIM simulation during part-load operation using data from previously published works that used Aspen HYSYS. On the other hand, the second case included performing a DWISM simulation using real filed data. The results gained were validated by comparing it with Aspen HYSYS simulation. The comparison between DWSIM and HYSYS showed a 3.8% variation in power generation, a close match in fuel flow, and a maximum variation of 4.36% in gas turbine efficiency. The findings of this work confirm that the DWSIM software is flexible, free, and reliable simulation tool for evaluating CCGT power plant’s performance and operation. In addition, this work presented that this software is suitable for use in both industrial and academic applications due to its performance compared to that of commercial simulators.